Enhancing MSMEs Performance in Gorontalo through Employee Development, Recruitment, and Job Satisfaction - Moh Rolli Paramata; Mohamad Afan Suyanto; Olfin Ishak; Ayub Usman Rasid; Anggita Permata Yakup (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are crucial drivers of economic growth, job creation, and equitable income distribution, particularly in developing regions such as Gorontalo, Indonesia. As engines of local innovation and contributors to poverty alleviation, the sustainability and competitiveness of MSMEs depend heavily on internal organizational factors, especially human resource management (HRM). This study explores the impact of employee development, recruitment, and job satisfaction on the performance of MSMEs in Gorontalo. A quantitative research approach was employed using Structural Equation Modeling with Partial Least Squares (SEM-PLS) to examine the relationships among these variables. Data were gathered from 94 MSME respondents from trade, manufacturing, and service sectors using purposive sampling. Results indicate that employee development (β = 0.306, p = 0.001), job satisfaction (β = 0.289, p = 0.039), and recruitment (β = 0.220, p = 0.034) significantly and positively impact performance, with employee development showing the strongest influence. Among these, employee development emerged as the most influential factor, emphasizing the importance of continuous skill enhancement and training initiatives. The results suggest that MSMEs must prioritize strategic HRM practices to strengthen organizational capabilities, even in semi-urban environments with limited resources. It also offers practical implications for policymakers and business owners by highlighting the need to invest in human capital as a pathway to achieving long-term performance and competitiveness. Future research is encouraged to explore additional HR dimensions and contextual variables influencing MSME success.